Development of skeletal system for mesh-type ICRP reference adult phantoms. (19th September 2016) - Yeom, Yeon Soo; Wang, Zhao Jun; Nguyen, Thang Tat; Kim, Han Sung; Choi, Chansoo; Han, Min Cheol; Kim, Chan Hyeong; Lee, Jai Ki; Chung, Beom Sun; Zankl, Maria; Petoussi-Henss, Nina; Bolch, Wesley E; et al.
Abstract: The reference adult computational phantoms of the international commission on radiological protection (ICRP) described in Publication 110 are voxel-type computational phantoms based on whole-body computed tomography (CT) images of adult male and female patients. The voxel resolutions of these phantoms are in the order of a few millimeters and smaller tissues such as the eye lens, the skin, and the walls of some organs cannot be properly defined in the phantoms, resulting in limitations in dose coefficient calculations for weakly penetrating radiations. In order to address the limitations of the ICRP-110 phantoms, an ICRP Task Group has been recently formulated and the voxel phantoms are now being converted to a high-quality mesh format. As a part of the conversion project, in the present study, the skeleton models, one of the most important and complex organs of the body, were constructed. The constructed skeleton models were then tested by calculating red bone marrow (RBM) and endosteum dose coefficients (DCs) for broad parallel beams of photons and electrons and comparing the calculated values with those of the original ICRP-110 phantoms. The results show that for the photon exposures, there is a generally good agreement in the DCs between the mesh-type phantoms and the original voxel-type ICRP-110 phantoms; that is, the dose discrepancies were less than 7% in all cases except for the 0.03 MeV cases, for which the maximum difference was 14%. On the other hand, for the electron exposures (⩽4 MeV), the DCs of the mesh-type phantoms deviate from those of the ICRP-110 phantoms by up to 1600 times at 0.03 MeV, which is indeed due to the improvement of the skeletal anatomy of the developed skeleton mesh models.